Perlindungan Hukum terhadap Pemegang Hak Merek Minyak Biawak yang Ditiru - Emir Syarif Fatahillah Pakpahan; Febyola Nababan; Lili Dianawati (Mahesa Research Center, 2022)
The purpose of this study was to find out the legal provisions or regulations regarding trademark rights according to the trademark law, violations and legal protection of registered trademarks and legal protection against holders of the rights to the copy of the Biawak oil mark. The research is focused on the legal protection of the rights holders of the lizard oil brand. In order to approach this problem, a reference to the theory of legal protection and the theory of legal certainty is used. Data was collected through document analysis, interviews and observations using a qualitative approach. Based on the findings in the field that the Legal Provisions or Regulations Regarding Mark Rights according to the Trademark Law are regulated in the Trademark Law and Geographical Indications. Violation and Legal Protection of registered Marks, may be subject to criminal, civil, and administrative law sanctions. Legal Protection for Copyright Holders of Imitated Biawak Oil. In this case, it demands compensation and the cessation of all use of the mark. The Commercial Court was sued (Article 76 paragraph 1 and paragraph 3 of the Trademark and Geographical Indication Law.